2020
DOI: 10.1016/j.heliyon.2020.e05430
|View full text |Cite
|
Sign up to set email alerts
|

New putative animal reservoirs of SARS-CoV-2 in Italian fauna: A bioinformatic approach

Abstract: SARS-CoV-2 is a virus belonging to the betacoronavirus family, causing fatal respiratory disease in humans, which became pandemic in 2020. Italy is one of the most affected countries by COVID-19, particularly in the northern regions. Several studies consider COVID-19 a zoonotic disease and, since Italy is the repository of a high biodiversity, SARS-CoV-2 infection in animals can be considered as a reservoir of the virus or favor the spreading between animals and humans. In this work, we analyzed the amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…A comprehensive phylogenetic analysis coupled with critical site comparison of the ACE2 receptor showed that several species, including civet, swine, pangolin, cat, cow, buffalo, goat, sheep and pigeon, may be susceptible to SARS-CoV-2 and serve as intermediate hosts [ 16 ]. Similar findings have been reported by other authors who have analyzed the amino acid sequences of the ACE2 receptor of a number of wild and domestic animals and concluded that horses, cats, cattle, sheep, European rabbits and grizzly bears may serve as potential SARS-CoV-2 secondary reservoirs [ 17 ]. Experimental studies have confirmed that inoculation of SARS-CoV-2 can cause infection of rabbits [ 18 ].…”
Section: Discussionsupporting
confidence: 88%
“…A comprehensive phylogenetic analysis coupled with critical site comparison of the ACE2 receptor showed that several species, including civet, swine, pangolin, cat, cow, buffalo, goat, sheep and pigeon, may be susceptible to SARS-CoV-2 and serve as intermediate hosts [ 16 ]. Similar findings have been reported by other authors who have analyzed the amino acid sequences of the ACE2 receptor of a number of wild and domestic animals and concluded that horses, cats, cattle, sheep, European rabbits and grizzly bears may serve as potential SARS-CoV-2 secondary reservoirs [ 17 ]. Experimental studies have confirmed that inoculation of SARS-CoV-2 can cause infection of rabbits [ 18 ].…”
Section: Discussionsupporting
confidence: 88%
“…The role of equids in the COVID-19 pandemic has remained poorly investigated. Horses are potentially susceptible to SARS-CoV-2 based on the binding affinity and stability between ACE-2 and the receptor-binding domain of the S protein [ 8 , 9 ]. Considering the large number of equids globally and the direct or indirect contact these animals have with humans, information pertaining to their susceptibility to SARS-CoV-2 and their role in virus transmission is needed.…”
Section: Introductionmentioning
confidence: 99%
“…A search for ACE2 sequence similarities in domestic and wild animals in Italy revealed domestic (horses, cats, cattle, and sheep) and wild (European rabbits and grizzly bears) animal species as potential SARS-CoV-2 secondary reservoirs. Molecular docking of these species’ ACE2 against the S protein of the Bat coronavirus (Bt-CoV/Rp3/2004) suggests that the primary reservoir Rhinolophus ferrumequinum may infect secondary reservoirs, domestic and animals living in Italy [ 81 ].…”
Section: Methodsmentioning
confidence: 99%